Can Desire and Wellbeing Be Promoted in Adolescents and Young Adults Affected by Cancer? PhotoTherapy as a Mirror That Increases Resilience - Testoni, Ines; Tomasella, Elena; Pompele, Sara; Mascarin, Maurizio; Wieser, Michael Alexander (Frontiers in Psychology, 2020)
PhotoTherapy represents a recent psychotherapeutic intervention which, through the medium of photography, has the objective of helping a patient reach a higher self-knowledge and explore thoughts, desires and intimate perceptions that would otherwise remain hidden. Because of this, it may help people overcome their cognitive and emotional boundaries and bring out their interiority, even when exploring some of the most distressing themes. The objective of the present research was to demonstrate that the elaboration and expression of inner desires, fears and needs of wellbeing among adolescents and young adults, who were either sick or had been cured of cancer, could be facilitated through the use of PhotoTherapy. Their responses were also compared with those of healthy young adults, in order to be able to explore the kind of impact such a pathology can have on those who are affected by it and highlight eventual differences in the kind of desires and needs expressed instead by those who never had a diagnosis of cancer. A qualitative research design was adopted. Forty-five people took part in the study, aged between 12 and 25 (mean age 19). The participants were divided into three groups: those currently being treated for cancer, those with a history of cancer and those who had no experience of cancer (third group). From the data analysis, different preferences and attitudes towards the presented pictures and themes emerged among the participants, depending on the specific group they belonged to. The article discusses these preferences and considers how PhotoTherapy can help treat psychological distress caused by cancer.